Evaluation parameters for computer aided design of irrigation systems - Todes, M A (Department of Civil Engineering, 2016)
The research has entailed the formulation and coding of computer models for the design of pressurized irrigation systems. Particular emphasis has been given to the provision of routines for the evaluation of the expected performance from a designed system. Two separate sets of models have been developed, one for the block or in-field system and one for file mainline netWork. The thesis is presented in three seelions asfollows : * Basic theory, in which the general background to the research is covered. * The models, which includes detailed descriptions of both the design models and the computer programs. * Applications, in which several test casesof both sets of models are reported.